PENGARUH BUDAYA ORGANISASI TERHADAP EMPLOYEE ENGAGEMENT PADA FAKULTAS EKONOMI DAN BISNIS SERTA FAKULTAS KOMUNIKASI DAN BISNIS UNIVERSITAS TELKOM - Suci Octaviani; Mahendra Fakhri (UIR Press, 2016)
Around the world that focus on employee engagement can outperform its competitors through some business outcomes. One of the factors that can increase employee engagement is the cultureof the organization. Telkom University itself is the result of a merger of four institutions underthe auspices of the Telkom Foundation. The merger led to the emergence of a new culture thatmust be applied. This research was conducted to determine the influence of organizationalculture on employee engagement in FEB and FKB Telkom University.The method used isquantitative descriptive research causal. The data collection is done by distributingquestionnaires to 37 lecturers in FEB and FKB Telkom University. Data collected will be testedfor simple linear regression analysis.Descriptive results showed that organizational culture andemployee engagement in FEB and FKB Telkom University are in the strong category. Based onthe test results showed that organizational culture influence on employee engagement in FEBand FKB Telkom University. Based on the results of this study concluded that organizationalculture influence on employee engagement in FEB and FKB Telkom University 43.1%, while56.9% are influenced by other factors not examined in this study.